ChemInform Abstract: Chemical, Pharmacological, and in vitro Metabolic Stability Studies on Enantiomerically Pure RC‐33 Compounds: Promising Neuroprotective Agents Acting as σ1 Receptor Agonists. Issue 4 (28th January 2014) - Collina, Simona; et al., et al.
Abstract Both RC‐33 enantiomers (III) show similar affinities for the σ1 receptor, but the (R)‐RC‐33 exhibits higher in vitro hepatic metabolic stability in the presence of NADPH.